Rancangan dan Implementasi Sistem Monitoring Bencana Frost (Embun Beku) - RAVYDO ANGGARA JUFRI; HAPSORO AGUNG NUGROHO; ARIES KRISTIANTO; DENI SEPTIADI; RISTA HERNANDI VIRGIANTO; IMMA REDHA NUGRAHEINI; ITA SOEGIARTO (Jurnal Elkomika)
ABSTRAK